PENGEMBANGAN PENGGUNAAN APLIKASI GEOMATH ROOM BERBASIS CIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATIC (STEM) PADA SISWA KELAS VIII DI SMPN 11 DENPASAR - Ni Made Winda Wijayanti; I Komang Sukendra; Ni Kadek Rini Purwati (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
Digital learning media provides many conveniences for teachers and students in making learning and teaching experiences more flexible. However, learning media has not been widely implemented in schools. The purpose of this research is (1) to determine the development of the geomath room application as a STEM-based digital learning media on spatial building materials. (2) to determine the quality of STEM-based geomath room applications in spatial building materials. This research uses research and development methods with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The product resulting from this research is Geomath Room-based digital learning media based on Science, Technology, Engineering, and Mathematics (STEM) with discussion material, namely building a room for class VIII junior high school students which is packaged in an application called geomath room. The data sources for this research are validators, mathematics teachers and students. Research data collection techniques use questionnaires and tests. Where the validity test results were declared valid with a percentage of material validation of 0.88 and media validation of 0.89. In the quality test the geomath room application was declared practical and effective. The percentage of student learning test results in limited trials was 70%, field trial I was 81.3%, and field trial II was 88%. The percentage results of student response questionnaires in limited trials were 65%, field trials I were 66%, and field trials II were 67%. So it can be concluded that the learning media in the form of a STEM-based geomath room application on spatial building material is valid, effective and practical.